Home Ice Rivals - Jake Maddox (Stone Arch Books, 2021)
Benji Krueger loves playing hockey with his friends at his home on Prairie Lake. But Benji's heart is broken when his parents announce that they're having a baby and the family will have to move. To make matters worse, his older sister, Raina, is a skilled hockey player and loves to embarrass Benji on the ice. When Benji learns about a pond hockey tournament by his house, he rallies his friends to take on his sister's team. Will Benji finally defeat his sister on their own home ice and learn to have confidence in his own abilities?
Keywords: Sport Stories -- Sport Stories